Impact of increasing amounts of supplemental high-protein soybean meal on performance of range beef cows - Mathis, C.P.; Cochran, R.C.; Woods, B.C.; Heldt, J.S.; Olson, K. C.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and twenty spring-calving Hereford × Angus cows grazing low-quality, tallgrass-prairie forage were fed 1.0, 1.5, 2.0, 2.5, 3.0, 4.0, 5.0, or 6.0 lb soybean meal (SBM) per head daily. SBM as a source of supplemental degradable intake protein (DIP) can be effective in maintaining cow body weight and body condition during the winter grazing season. Performance as measured by changes in body weight and condition score was maximized when cows received approximately 3.5 to 3.8 lb/day. Below this level, cows lost about 48 lb (about .4 units of BCS) for every 1 lb decrease in the amount of supplemental SBM. The effect of amount of supplemental SBM on calf performance was minimal.
Keywords: Beef; Range cows; Forage; Soybean meal